PENGARUH INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Septhia Irefan; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2018)
This study aims to identify and analyze the effect (1) The telecommunications infrastructure, (2) road infrastructure, and (3) air transport infrastructure to economic growth in Indonesia Estimates data using regression panel data analysis with the data period 2012-2016. The estimation results show that (1) Telecommunications infrastructure has a positive and significant impact on economic growth in Indonesia, (2) Road infrastructure positive and significant impact on economic growth in Indonesia, (3) Air transport infrastructure positive and significant impact on economic growth in Indonesia. Taken together telecommunications infrastructure, road infrastructure, air transport infrastructure significantly influence economic growth in Indonesia at α = 5%.